Deforestation Trends and Drivers in Central Halmahera Regency - B, Sabaruddin; Kurniawan, Andy; Arif, Nurfadhilah (Jurnal Wasian, 2024)
Land use patterns are strongly influenced by human requirements; among the most important problems is deforestation. Particularly with deforestation, central Halmahera Regency has seen significant changes in land usage. We use Qgis software and remote sensing data, to seeks and identify the rate of deforestation in Central Halmahera Regency. from Global Forest Change, that satellite pictures data. According to this studies, Weda and Maba were the most impacted areas in Central Halmahera experiencing the worst deforestation between 2014 and 2017. The conversion of forest land into nickel mining sites caused notable destruction in several places. With an average annual loss of 1,435.43 hectares between 2001 and 2013, data showing varying rates of deforestation between 2001 and 2022 shows Rising during 2014 and 2015, the pace of deforestation peaked at 8,852.506 hectares but started to fall in 2016 and 2017.